Peran Stomata dalam Proses Pertukaran Gas pada Rhoeo Discolor - Anisyah Trieka Salsa Nabila; Bilqis Oktasya Ditya; Eka Nur Damayanti; Ferisha Natalia Christine; Reni Puji Kristanti; Yudea Rambu Atha Randjapati; Liss Dyah Dewi Arini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Stomata are microscopic pores located on the surface of leaves that play a significant role in plant physiological processes, particularly photosynthesis and transpiration. These structures regulate the exchange of gases between plants and the surrounding environment, thereby supporting plant growth and survival. This study aims to analyze the role of stomata in the gas exchange process of Rhoeo discolor using the Systematic Literature Review (SLR) method. The review process involved identifying, selecting, evaluating, and synthesizing various scientific articles related to stomatal structure, function, and physiological mechanisms in plants. Relevant literature was collected from scientific journals discussing stomata and plant physiological activities. The findings of the review indicate that stomata in Rhoeo discolor function as the primary regulators of carbon dioxide (CO₂) uptake and oxygen (O₂) release during photosynthesis. In addition, stomata are responsible for controlling water vapor loss through the transpiration process, which is essential for maintaining water balance within the plant. The opening and closing mechanisms of stomata are influenced by several internal and external factors, including light intensity, temperature, water availability, humidity, and atmospheric CO₂ concentration. These factors affect guard cell activity, which determines stomatal movement. Furthermore, stomata contribute to maintaining physiological stability and optimizing metabolic processes in plants. Based on the reviewed literature, it can be concluded that stomata play a crucial role in enhancing the efficiency of gas exchange and supporting the overall physiological performance of Rhoeo discolor plants.